An evaluation of the effectiveness of an english language teaching methodology course for selected non-option secondary school teachers in Northern Perak - Ilengoven, A / L S. Krishnasamy. (2000)
The aim of this study was to evaluate the effectiveness of the English Language Teaching Methodology course for selected non-option teachers who were teaching English at secondary schools in Northern Perak as perceived by them.